Expresionism, (neo)expresionism în poezia română – o scurtă istorie a receptării - Raluca Dună (Revista de Istorie și Teorie Literară)
This study follows the history of Expressionism in Romanian culture, how the concept was introduced in Romanian poetry and how it was interpreted and practiced by poets and critics altogether. It is partly focused on the case of Lucian Blaga, our interwar expressionist poet, but who managed to incorporate into his poetry only some features, not the essence of original Expressionism. The reception of Expressionism, during postwar period, was influenced by the incongruent equivalence between Blaga and Expressionism. The study focused then on the reception of NeoExpressionism during the 70s and how later critics from the 80s misinterpreted Expressionism. The last section of this history covers the last decade, when Transylvanian critics like Al. Cistelecan and Ion Pop expressed their confidence into a neoexpressionist poetry, practiced by the young poets of the 2000s, which emerged from a marginal line of the 80s poetry, best represented by Ion Mureșan.